The Effect of Telenursing on the Quality of Life of Chronic Kidney Disease Patients Undergoing Hemodialysis: A Systematic Literature Review - Fatimatus Zahron Faizin; Fitri Arofiati (The Indonesian Institute of Science and Technology Research, 2026)
Chronic Kidney Disease (CKD) is a growing global health issue that significantly impacts renal function and patients' quality of life, particularly those undergoing hemodialysis. Patients' quality of life is influenced by clinical, psychological, and environmental factors, where limited access to healthcare services often presents a barrier. Telenursing has emerged as a health technology innovation to provide remote nursing care to support disease management. This study aims to synthesize the effect of telenursing on the quality of life of CKD patients undergoing hemodialysis. The method used was a literature review searching articles via international databases Scopus, ProQuest, and PubMed. The search was limited to full-text English articles published between 2019 and 2024 using the keywords